Oxide-confined VCSELs fabricated with a simple self-aligned process flow. (26th October 2017) - Marigo-Lombart, L; Calvez, S; Arnoult, A; Thienpont, H; Panajotov, K; Almuneau, G
Abstract: We propose a simplified and easier fabrication process flow for the manufacturing of AlO x -confined vertical-cavity surface-emitting lasers (VCSELs) based on combining the oxidation step with a self-aligned process, allowing the mesa etching and two successive lift-off steps based on a single lithography step. The electro-optical confinement achieved by standard lateral oxidation enables a low threshold and a single mode behavior for the VCSEL. This simplified process can largely improve VCSEL manufacturing by reducing the processing time and costs compared to the standard VCSEL process.